Learners' and teachers' acceptance of mobile learning: an exploratory study in a developing country. (20th September 2021) - Mutambara, David; Bayaga, Anass
The current study used the technology acceptance model (TAM) to examine learners' and teachers' acceptance of mobile learning of science, technology, engineering, and mathematics (STEM) in a developing country. A total of 160 learners and 100 teachers were selected using stratified random sampling to participate in this study. Quantitative methods, including structural equation modelling data analysis, were employed to examine STEM learners' and teachers' attitudes towards mobile learning, and to investigate factors that learners and teachers consider important when accepting mobile learning in STEM. The results indicated that both teachers and learners have a positive attitude towards mobile learning. Additionally, there is no significant difference between teachers' and learners' attitudes towards mobile learning. The implication is that developers of mobile learning systems should make their platforms easy to use and also have more resources available for both teachers and learners to increase the overall acceptance of mobile learning in STEM.